The 4D evolution of the All on X digital workflow - Dr Konstantinos Kountouras (Elsevier, 2023)
Introduction: Recent digital technological advances have allowed for any All-on-X full arch implant case to be digitally planned.Adopting a workflow that involves the creation of a virtual patient by combining digital records of intraoral scans, face scans, CBCT, digital tracking of the patients own mandibular movements and optical impression of the implant positions could ensure not only an optimal treatment planning but also the best fit of the future implant prosthesis.Nevertheless, only when this advanced digital workflow is combined with some well-established traditional prosthetic principles of treatment, long term predictable clinical results could be achieved. Case Description: A case report of a patient seeking an All-on-X full arch implant rehabilitation is described. The steps taken to transform the real patient to a complete virtual patient are outlined. Special emphasis is given to the way that traditional prosthetic full mouth rehabilitation principles were incorporated to the digital workflow for predictable functional and aesthetic results to be achieved. Discussion: Establishing the correct treatment position is of paramount importance to the success of any All-on-X full arch implant prosthesis. Assembling a virtual patient and designing the prosthesis using the patients own mandibular movements could:- Help design the most appropriate shape of the prosthesis and its occlusal morphology- Lead to increased predictability from the virtual design to actual outcomes- Save chair time as less adjustments would be generally needed. Conclusion/Clinical Significance: The use of a virtual patient model using an established and confirmed optimal treatment position will lead to long term successful outcomes in any All-on-X implant case.